2024
DOI: 10.3390/su16052222
|View full text |Cite
|
Sign up to set email alerts
|

G20 Tourism Carbon Footprint and COVID-19 Impact

Akihiko Tsutsumi,
Ryuzo Furukawa,
Yusuke Kitamura
et al.

Abstract: The Glasgow Declaration called for scientifically based measurements of CO2 emissions in the tourism industry to monitor progress toward the achievement of the goals of the Paris Agreement. Despite the economic and employment downturn caused by COVID-19, there are limited cases of environmental assessments related to tourism. In this study, we estimated the CFP of the tourism industry in the G20 countries before and after COVID-19. By combining the MRIO and Tourism Satellite Accounts, we clarified the differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%
“…The above has revealed that, in recent years there has been a notable increase in the number of studies analysing the impact of the pandemic and its consequences on society and the environment [28][29][30][31][32]. Key topics have been the lockdown's effect on the environment, changes in product demand, plastic usage, and the subsequent increase in waste.…”
Section: Covid-19 and Environmental Efficiency In The Hospital Sectormentioning
confidence: 99%